ACESSIBILITY IN THE RECREATIONAL SPORTS CLUBS IN THE CITY OF CASCAVEL – PARANÁ (Fiep Bulletin - online, 2016)
This study intend to identify if the main recreational sports clubs in the city of Cascavel – PR have accessibility to disabled people (wheelchair users) on their facilities. The study is a field descriptive research. The data was collected through a technical visit conducted by the researchers along with a physically disabled person (wheelchair user) to point out the difficulties found in the environment. An observation card was used to report the limitations found by the handicapped during the visit at the analyzed club. With the investigation, it was found that the club needs a lot of structural changes in order to receive people with physical disabilities. Given that, much of the clubs does not offer good access conditions to allow a person with physical disability (wheelchair user) to transit through the place with autonomy, hindering this person to enjoy the benefits and the infrastructure offered to the club members on the leisure time.
Keywords: recreational sports clubs; physical disabilities (wheelchair users); leisure.